The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1172/jci42358
|View full text |Cite
|
Sign up to set email alerts
|

Conditional ablation of Ikkb inhibits melanoma tumor development in mice

Abstract: Several lines of evidence suggest that tumor cells show elevated activity of the NF-κB transcription factor, a phenomenon often resulting from constitutive activity of IκB kinase β (IKKβ). However, others have found that loss of NF-κB activity or IKKβ is tumor promoting. The role of NF-κB in tumor progression is therefore controversial and varies with tumor type. We sought to more extensively investigate the role IKKβ in melanoma tumor development by specifically disrupting Ikkb in melanocytes in an establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 77 publications
4
78
0
Order By: Relevance
“…Although the response to altered NFkB activity varies among different cell types, increased NFkB activity is usually associated with tumor development (1,32). IKKb also acts as a tumor promoter in different cell types, as it happens in colitis-associated cancer and melanoma development in animal models, as well as in human breast cancer patients (33)(34)(35). In the case of oral epithelia, we have observed inflammation and basal cell damage as a consequence of targeted overexpression of IKKb.…”
Section: Discussionmentioning
confidence: 71%
“…Although the response to altered NFkB activity varies among different cell types, increased NFkB activity is usually associated with tumor development (1,32). IKKb also acts as a tumor promoter in different cell types, as it happens in colitis-associated cancer and melanoma development in animal models, as well as in human breast cancer patients (33)(34)(35). In the case of oral epithelia, we have observed inflammation and basal cell damage as a consequence of targeted overexpression of IKKb.…”
Section: Discussionmentioning
confidence: 71%
“…This releases the p65/p50 NF-κB heterodimer, allowing its nuclear translocation and promoter binding for inflammatory gene transcription. A series of studies has indicated a requirement of Ikk2 and p65 in both murine and human Kras-induced transformation of lung epithelial cells and in models of inflammation-induced carcinogenesis (7,8,10,11). However, the implication of the pathway in pancreatic cancer has so far been unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Many cancer cell lines, but also primary tumors, display constitutively increased NF-κB activity, and inhibition of NF-κB compromises the survival and growth of cultured cancer cells, suggesting that NF-κB is important for the survival of at least some types of tumors (1). Furthermore, NF-κB inhibition diminished tumor development in mouse models, supporting an important role for NF-κB in carcinogenesis (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…However, NF-κB inhibition in skin or liver cells had opposite effects in different models of carcinogenesis. NF-κB inhibition by expression of IκBα-SR in epidermal keratinocytes synergized with oncogenic Ras to induce epidermal cancer (11) or led to spontaneous tumor development (12), while IKK2 ablation in melanocytes protected mice from oncogenic Ras-induced melanoma development (2). Moreover, NF-κB blockade by IκBα-SR expression in hepatocytes inhibited inflammation-associated liver cancer development in the Mdr2-deficient mouse model (3), while IKK2 ablation in hepatocytes sensitized mice to chemical hepatocarcinogenesis induced by diethylnitrosamine (DEN) (13).…”
Section: Introductionmentioning
confidence: 99%